2007
DOI: 10.1029/2006gl029127
|View full text |Cite
|
Sign up to set email alerts
|

A five‐year analysis of MODIS NDVI and NDWI for grassland drought assessment over the central Great Plains of the United States

Abstract: [1] A five-year (2001 -2005) history of moderate resolution imaging spectroradiometer (MODIS) normalized difference vegetation index (NDVI) and normalized difference water index (NDWI) data was analyzed for grassland drought assessment within the central United States, specifically for the Flint Hills of Kansas and Oklahoma. Initial results show strong relationships among NDVI, NDWI, and drought conditions. During the summer over the Tallgrass Prairie National Preserve, the average NDVI and NDWI were consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
308
0
18

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(334 citation statements)
references
References 22 publications
8
308
0
18
Order By: Relevance
“…This NDWI is the variation developed by Gao (1996). The study conducted by Gu et al (2007) showed that NDWI has a stronger response to drought conditions than NDVI. The average of NDVI and NDWI were consistently lower (NDVI<0.5 and NDWI<0.3) under drought conditions than under nondrought conditions (NDVI>0.6 and NDWI>0.4) At shallow, turbid waters the water-leaving reflectance at NIR is not negligible, and is not only related to phytoplankton abundance, but also to suspended sediment concentration.…”
Section: Characterization Of Spectral Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This NDWI is the variation developed by Gao (1996). The study conducted by Gu et al (2007) showed that NDWI has a stronger response to drought conditions than NDVI. The average of NDVI and NDWI were consistently lower (NDVI<0.5 and NDWI<0.3) under drought conditions than under nondrought conditions (NDVI>0.6 and NDWI>0.4) At shallow, turbid waters the water-leaving reflectance at NIR is not negligible, and is not only related to phytoplankton abundance, but also to suspended sediment concentration.…”
Section: Characterization Of Spectral Indicesmentioning
confidence: 99%
“…A new method for drought delineation using MODIS surface reflectance data was presented in the paper by Gu et al (2007) Rouse et al (1973), and it has been in use for decades for monitoring vegetation cover, chlorophyll content and other properties of the plants. Absorption of healthy vegetation is very high in the visible wavelength range.…”
Section: Characterization Of Spectral Indicesmentioning
confidence: 99%
“…The Normalized Difference Water Index (NDWI) is commonly used as an accurate estimate of plant water content [10]. It has been successfully applied to the remote detection of plant water content for grasslands [11]. Enhanced Vegetation Index (EVI) is an "optimized" index designed to enhance the vegetation signal with improved sensitivity in high biomass region, and it is also an improvement of vegetation monitoring through de-coupling of the canopy background signal and a reduction in atmospheric influences [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The time interval of these pictures is eight days and accessible for peninsular region of India. These images are for free of cost, pre calibrated and cleaned for cloud effects using the maximum NDVI method (Holben, 1986;King et al, 2003 (Gu et al, 2007). Using this concept, NDVI can be defined as the ratio of difference of near infrared and red to its sum.…”
Section: Methodsmentioning
confidence: 99%